2020
DOI: 10.4049/jimmunol.1900954
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Augments Antigen-Induced Murine Mast Cell Degranulation and Allergic Responses via P2X4 Receptor Activation

Abstract: Extracellular ATP released from stimulated and/or damaged cells modulates physiological responses via stimulation of various purinoceptors. We previously showed that ATP potentiated the Ag-induced mast cell (MC) degranulation via purinoceptors pharmacologically similar to the ionotropic P2X4 receptor. In this study, we investigated the role of P2X4 receptor in MC degranulation induced by stimulation of IgE-Fc«RI complex with Ag, using bone marrow-derived MCs (BMMCs) prepared from wild type and P2X4 receptor-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
(60 reference statements)
1
33
0
Order By: Relevance
“…To answer this question in the P2X4 ko mice, one would need to compare P2X7 expression on innate immune cells from the different P2X4-deficient strains. Interestingly, P2rx7 mRNA expression level in BMMCs from the P2rx4 tm1Ando strain (Yamamoto et al, 2005) where comparable to those of B6 WT BMMCs (Yoshida et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…To answer this question in the P2X4 ko mice, one would need to compare P2X7 expression on innate immune cells from the different P2X4-deficient strains. Interestingly, P2rx7 mRNA expression level in BMMCs from the P2rx4 tm1Ando strain (Yamamoto et al, 2005) where comparable to those of B6 WT BMMCs (Yoshida et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Previously, we demonstrated that P2X4R stimulation promotes Ag-induced tyrosine phosphorylation signaling, providing a possible mechanism for synergistic MC degranulation in response to Ag and ATP [13]. However, this mechanism was not involved in the effect of ATP and PGE 2 on MC degranulation, since the response to ATP and PGE 2 was insensitive to the tyrosine kinase inhibitor PP2 or Syk inhibitor R406, both of which inhibited the synergistic degranulation induced by Ag and ATP.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, degranulation induced by ATP and PGE 2 was inhibited by the non-selective PI3K inhibitor LY294002 and PI3Kγ selective inhibitor AS605240; however, ATP did not enhance PGE 2 -induced Akt phosphorylation but rather decreased it slightly. Although ATP itself slightly stimulates Akt phosphorylation, this effect is unchanged in P2X4R KO mice [13], suggesting that ATP-induced Akt phosphorylation is mediated by a receptor other than P2X4R and that P2X4R stimulation does not affect Gβγ-mediated PI3Kγ activation. These results suggest that PI3Kγ activation is necessary for ATP and PGE 2 -induced degranulation but that the downstream mechanism differs to that described for the combination of Ag and PGE 2 [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that ATP and BzATP (a P2X agonist) increased calcium in human MCs and induced MC degranulation by activating P2X7 receptors [140][141][142]. The P2X4 receptor plays an essential role in ATP-induced upregulation of MC degranulation in response to Ag, and also promotes the Ag-induced systemic and intradermal passive anaphylaxis responses in vivo [143]. Moreover, activation of the P2X4 receptor (P2X4R) is involved in the synergistic effect of prostaglandin (PG) E2 and ATP on murine MC degranulation [144].…”
Section: Adenosine Triphosphate Regulation Of Mast Cellsmentioning
confidence: 99%